2021
DOI: 10.48550/arxiv.2108.07734
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Short proofs of rainbow matching results

Abstract: A subgraph of an edge-coloured graph is called rainbow if all its edges have distinct colours. The study of rainbow subgraphs goes back to the work of Euler on Latin squares and has been the focus of extensive research ever since. Many conjectures in this area roughly say that "every edge coloured graph of a certain type contains a rainbow matching using every colour". In this paper we introduce a versatile "sampling trick", which allows us to obtain short proofs of old results as well as to solve asymptotical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…Recently, the two authors together with Pokrovskiy [16] showed that v m ≤ 2n + 2m + O(n/(log n) 1/4 ). This substantially improves the result in [17] and is asymptotically tight for m = εn and log −1/4 n ≪ ε ≪ 1.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Recently, the two authors together with Pokrovskiy [16] showed that v m ≤ 2n + 2m + O(n/(log n) 1/4 ). This substantially improves the result in [17] and is asymptotically tight for m = εn and log −1/4 n ≪ ε ≪ 1.…”
Section: Discussionmentioning
confidence: 99%
“…Our first step in the proof of Theorem 1.2 will be in this direction. We will show that in any (n, v)multigraph with multiplicity at most (1− δ)n and with v close enough to 3n, we can always find a rainbow matching of size n. In order to prove this, we will first show that one can find a rainbow matching of size n − f (δ), which is a quick corollary of Lemmas 2.9 and 2.10, and then use the sampling trick introduced in [16] to transform this into a result giving a full rainbow matching.…”
Section: An Outline Of the Proofmentioning
confidence: 94%
See 3 more Smart Citations